Linkages of Electoral Accountability: Empirical Results and Methodological Lessons - Maloy, J. S. (2014)
A basic theory of electoral accountability is widely accepted by academic opinion: voters cause politicians to gain or lose office through periodic elections, thereby influencing policy through the threat of electoral sanction. Empirical studies run the gamut from findings of strong support for this theory, to mixed or conditional support, to weak or negative results. When electoral processes are analyzed in terms of two distinct causal linkages within a three-part chain of accountability, however, positive findings are revealed as weaker than they appear while a compelling trend emerges toward findings ranging from conditional to negative in the last two decades. This trend is visible in three topical areas—economic voting, political corruption, and ideological congruence—and it holds for both presidential and parliamentary regimes as well as for a variety of electoral systems. The new electoral skepticism’s unsettling results and insightful methods may help to improve future research and reform efforts alike.